Inspiracion para vivir : inspiration for life - Haro Lebrija, Fernando de; Fuentes, Omar (Am Publishers, 2009)
Offers an inspiring look at the work of some of Mexico's very best contemporary architects. This title showcases how they rise to the challenge of designing a space to live in. It is suitable for architects and designers looking for that little bit of inspiration